Ein Ansatz zur Bewertung klimapolitischer Instrumente am Beispiel der Metallerzeugung und -verarbeitung - Breun, Patrick (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2016)
Achieving the ambitious greenhouse gas (GHG) reduction targets set up by German legislation requires political incentives to reduce GHG emissions of energy intensive industries without hampering their international competitiveness. This dissertation therefore analyses the influence of different political instruments (ETS, EEG, EnergieStG, StromStG) on induced emission reductions as well as on relevant economic parameters. Thereby, the focus is set on the metal production.